2018
DOI: 10.1002/etc.4281
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic exposure to environmentally relevant concentrations of triclosan impairs foraging efficiency in zebrafish larvae

Abstract: The ubiquitous and persistent contaminant triclosan is known to cause developmental and behavioral toxicity in fish, but few studies have evaluated the long‐term effects of these responses. We used a phenotypically anchored approach to evaluate the behavioral responses caused by early exposure to environmentally relevant concentrations of triclosan to better understand the risk triclosan poses to fish. Zebrafish were exposed to 0, 0.4, 4, or 40 μg triclosan/L (nominal concentrations) for 5 d followed by depura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…This is in line with observations by Kim et al ( 2018 ), who described a smaller eye diameter in zebrafish exposed to TCS. A decrease in eye diameter was also evident in zebrafish embryos exposed to other TPO inhibitors such as PTU (Baumann et al 2016 , Reider and Connaughton 2014 ) and could be correlated to impaired foraging efficiency of zebrafish embryos after exposure to TCS (Wirt et al 2018 ). Whereas the thickness of the RPE did not respond to TCS exposure, changes in PRL thickness showed a monotonic increase over water and DMSO controls with increasing TCS concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with observations by Kim et al ( 2018 ), who described a smaller eye diameter in zebrafish exposed to TCS. A decrease in eye diameter was also evident in zebrafish embryos exposed to other TPO inhibitors such as PTU (Baumann et al 2016 , Reider and Connaughton 2014 ) and could be correlated to impaired foraging efficiency of zebrafish embryos after exposure to TCS (Wirt et al 2018 ). Whereas the thickness of the RPE did not respond to TCS exposure, changes in PRL thickness showed a monotonic increase over water and DMSO controls with increasing TCS concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Once triclosan levels are detected in various human tissues such as adipose tissue, brain, and liver [ 55 , 56 ], studies on its long-term effects on human health have been undertaken [ 57 ]. Toxic effects of triclosan have been also extensively evaluated using zebrafish as an animal model [ 58 , 59 , 60 , 61 ]. Triclosan’s mechanisms of toxicity encompass a range of effects on zebrafish, including endocrine disruption, oxidative stress, microbiota imbalance, altered behavior, and developmental and reproductive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced eye size, an indicator of neurotoxicity, was also observed in zebrafish embryos exposed to more than 0.4 μg/L triclosan. [ 63,68 ]…”
Section: Triclosan Induced Neurotoxicitymentioning
confidence: 99%
“…Reduced eye size, an indicator of neurotoxicity, was also observed in zebrafish embryos exposed to more than 0.4 μg/L triclosan. [63,68] Several studies have reported triclosan-induced neurotoxicity using cell culture as experimental system. Triclosan-induced apoptosis in mouse neocortical neurons, mouse neuronal progenitor cells, and rat neural stem cells.…”
Section: Triclosan Induced Extensive Morphological Changes In the Ner...mentioning
confidence: 99%